DEVELOPING STUDENTS TEXT CREATION SKILLS IN LANGUAGE TEACHING - Humoyun Abdulahad ugli Umaraliyev (Galaxy International Interdisciplinary Research Journal, 2022)
The only way to pass on to future generations the scientific resources necessary for the socio-political development of mankind is to study the text and the science of creation. So language is opportunity and text is result; the product of the knowledge, skills, and competencies acquired by the text.